Balancing intrinsic properties of cathode materials allows high performance for protonic ceramic fuel cells - Yanru Yin; Bo Liu; Dong Yan; Jian Li; Lichao Jia (SusMat)
Abstract The cathode performance significantly impacts the overall performance of protonic ceramic fuel cells (PCFCs). Many properties of the material, such as oxygen vacancies, protonation, charge carrier transport abilities, and surface oxygen reduction reaction activity, can affect cathode performance. However, which parameter has more weight is still being debated. In this work, we use Ba0.5Sr0.5Zr0.25Fe0.65X0.1O3 as a case study (X = Zn, Cu, Mn, Ni, and Co). First‐principle calculations and experimental research are used to study and compare the critical parameters that determine cathode performance. It is discovered that no dopant can improve all the properties of the material. Balancing distinct intrinsic properties is a viable and rational approach. The more balanced, the better performance. When compared to other dopants, nickel dopant is shown to be the most effective in the Ba0.5Sr0.5Zr0.25Fe0.65X0.1O3 material system, allowing a high fuel cell performances of 1862, 1450, and 1085 mW cm−2 at 700°C, 650°C, and 600°C, with a low polarization resistance of 0.041 Ω cm2 at 700°C, which is higher than the majority of cobalt‐free cathodes for PCFCs. The current study not only presents a promising cathode candidate, but more importantly, also an effective and fundamental methodology to design cathodes for PCFCs.